Effect of Type 2 Diabetes Mellitus on Pulmonary Function - Huang, H.; Guo, Q.; Li, L.; Lin, S.; Lin, Y.; Gong, X.; Yao, J.; Liang, J.; Lin, L.; Wen, J.; Chen, G. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Background: Type 2 diabetes mellitus (T2DM) is a metabolic disease with debilitating effects on multiple organs. The alveolar-capillary network in the lung is a large microvascular unit which may be affected by T2DM-associated microangiopathy.Methods: This retrospective study investigated whether type 2 diabetes mellitus (T2DM) affected pulmonary function. Of the 584 patients enrolled in the study, 292 had T2DM and 292 did not. Forced expiratory volume in one second (FEV₁), forced vital capacity (FVC), maximum voluntary ventilation (MVV) and total lung capacity (TLC) are values as percent of predicted, as well as FEV₁/FVC ratio which were values measured.Results: FEV₁, FVC, FEV₁/FVC ratio, MVV, and TLC were significantly lower in T2DM than in non-T2DM (P-values<0.010). Multiple linear regression analysis found that for the entire study population fasting plasma glucose levels was negatively associated with FEV₁, FVC, FEV₁/FVC ratio and maximum voluntary ventilation (P-values<0.030). Patients with T2DM were negatively associated with total lung capacity (P-values=0.025). Multiple linear regression analysis found for patients with T2DM that fasting plasma glucose was negatively associated with FEV₁, FVC, FEV₁/FVC ratio and maximum voluntary ventilation (P-values<0.020). In T2DM patient, height was negatively correlated with FEV₁ and FVC (all P-values<0.020), triglycerides were negatively correlated with FEV₁/FVC ratio (P-values=0.048), and creatinine was negatively correlated with total lung capacity (P-values=0.017).Conclusions: In summary, T2DM is associated with impaired pulmonary function consistent with obstructive ventilation pattern and fasting plasma glucose is an independent risk factor of reduced pulmonary function.
Keywords: blood glucose; pulmonary function; type 2 diabetes mellitus